Development of an in vitro pump: mechanical characterization and surface engineering of elastomeric membranes - Paik, Isha (2013)
In vitro modelling offers the potential of recapitulating human degenerate tissue for physiological studies and pharmacological screening. Yet, few systems have been developed to date, primarily due to the lack of vascularisation in engineered tissue. Here, the development of an in vitro pump is addressed. This will be the first component of a long term strategy to build internal circulatory systems for in vitro engineered tissue. Firstly, mechanical characterisation and surface biocompatibility of spin coated poly(dimethylsiloxane) (PDMS) elastomeric membranes was investigated to assess whether PDMS could be used as a structural constituent. Results showed that spin coating speed defines both film thickness and specific mechanical properties since tensile testing revealed that PDMS membranes exhibit thickness-dependent mechanical properties. Plasma polymerisation of allylamine was used to surface engineer the hydrophobic PDMS surface to promote cell adhesion and proliferation. Surface characterisation revealed that PDMS surfaces became hydrophilic and nitrogen enriched as a result of plasma polymerised allylamine (ppAAm) deposition. Additionally, a thick ppAAm deposition (92 nm) is required to minimise hydrophobic recovery of PDMS. Cell culture studies showed that cells readily attached to ppAAm (92 nm) deposited PDMS and that these surfaces were best suited to cultivating cells compared to other surface treatments.